Dietary advice and oral nutritional supplements do not increase survival in older malnourished adults: a multicentre randomised controlled trial. (2nd July 2020) - Söderström, Lisa; Rosenblad, Andreas; Bergkvist, Leif; Frid, Hanna; Thors Adolfsson, Eva
Abstract: Objectives: The study aimed to investigate the effect on survival after 6 months of treatment involving individual dietary advice and oral nutritional supplements in older malnourished adults after discharge from hospital. Methods: This multicentre randomised controlled trial included 671 patients aged 65 years who were malnourished or at risk of malnutrition when admitted to hospital between 2010 and 2014, and followed up after 8.2 years (median 4.1 years). Patients were randomised to receive dietary advice or oral nutritional supplements, separate or in combination, or routine care. The intervention started at discharge from the hospital and continued for 6 months, with survival being the main outcome measure. Results: During the follow-up period 398 (59.3%) participants died. At follow-up, the survival rates were 36.9% for dietary advice, 42.4% for oral nutritional supplements, 40.2% for dietary advice combined with oral nutritional supplements, and 43.3% for the control group (log-rank test p = 0.762). After stratifying the participants according to nutritional status, survival still did not differ significantly between the treatment arms (log-rank test p = 0.480 and p = 0.298 for the 506 participants at risk of malnutrition and the 165 malnourished participants, respectively). Conclusions: Oral nutritional supplements with or without dietary advice, or dietary advice alone, do not improve the survival of malnourished older adults. These results do not support the routine use of supplements in older malnourished adults, provided that survival is the aim of the treatment. Trial registration: ClinicalTrials.gov with ID: NCT01057914